2023
DOI: 10.1073/pnas.2219475120
|View full text |Cite
|
Sign up to set email alerts
|

Neutral sphingomyelinase 2 is required for HIV-1 maturation

Abstract: HIV-1 assembly occurs at the inner leaflet of the plasma membrane (PM) in highly ordered membrane microdomains. The size and stability of membrane microdomains is regulated by activity of the sphingomyelin hydrolase neutral sphingomyelinase 2 (nSMase2) that is localized primarily to the inner leaflet of the PM. In this study, we demonstrate that pharmacological inhibition or depletion of nSMase2 in HIV-1-producer cells results in a block in the processing of the major viral structural polyprotein Gag and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The putative lipid-binding pocket in SER5 can bind cholesterol, cardiolipin, and other lipids [75]. Lipids, such as cardiolipin, PIP2, and SM have been implicated in HIV-1 fusion [76][77][78] and infection, and while SER5 does not appear to affect the overall lipid composition of virions [26], scrambling or redistribution of these lipids can have deleterious effects on viral fusion, leading to infectivity reduction. Indeed, it is known that SER5 can modulate Env conformation and predispose them to premature inactivation, and a lipid-mediated, indirect mechanism, as discussed above, is plausible [21,53].…”
Section: Discussionmentioning
confidence: 99%
“…The putative lipid-binding pocket in SER5 can bind cholesterol, cardiolipin, and other lipids [75]. Lipids, such as cardiolipin, PIP2, and SM have been implicated in HIV-1 fusion [76][77][78] and infection, and while SER5 does not appear to affect the overall lipid composition of virions [26], scrambling or redistribution of these lipids can have deleterious effects on viral fusion, leading to infectivity reduction. Indeed, it is known that SER5 can modulate Env conformation and predispose them to premature inactivation, and a lipid-mediated, indirect mechanism, as discussed above, is plausible [21,53].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings that ceramide is required for capsid maturation in HIV-1, it was recently observed that the inhibition of neutral sphingomyelinase 2, the rate-limiting enzyme of ceramide biosynthesis, prevented the full maturation of HIV-1 capsids and full infectivity in vitro [ 38 ] and in vivo [ 39 ].…”
Section: Other Rna Virusesmentioning
confidence: 99%
“…PDDC, an inhibitor of neutral sphingomyelinase 2 that prevents ceramide biosynthesis, was shown to block the maturation and full infectivity of HIV-1 particles [ 38 , 39 ].…”
Section: Compounds Interfering With Lipidome Homeostasismentioning
confidence: 99%